Circumstances of the Fourth-Century AD Reforms in North Africa (Revue El-Wahat pour les Recherches et les Etudes, 2026)
If the period preceding the fourth century AD was known for development and revival for the Roman Empire, then specifically starting from the third century it was the opposite, as it witnessed a storm that shook the throne of the entire empire. The starting point was the military chaos after the death of Emperor Alexander Severus in 235 AD, in which the army played a major role, during which it was in control and interfered in the affairs of power, in a struggle for control without regard for the consequences of this situation on the empire. It was natural that this crisis would affect the provinces of the empire, including the province of Africa. It too witnessed disturbances that began with the revolution of 238 AD and the spread of revolutions here and there. From the economic side, we find that the region experienced monetary inflation and agricultural, industrial and commercial deterioration, except for the products on which Rome depended heavily. As for the administrative side, we find that the African province had two types of provinces, imperial and senatorial, and four different systems of provinces. This created a social stratification that rejected reality and began to declare that rejection and resistance by establishing itself with its local culture and religions, and if necessary, even militarily by participating in rebel movements.  It became clear that the conditions of the third century, with all their calamities and devastation, had to be rectified within the framework of what is known as the reforms of the fourth century AD.